Unveiling the CHO surfaceome: Identification of cell surface proteins reveals cell aggregation‐relevant mechanisms. Issue 8 (14th May 2021) - Klingler, Florian; Mathias, Sven; Schneider, Helga; Buck, Theresa; Raab, Nadja; Zeh, Nikolas; Shieh, Yu‐Wei; Pfannstiel, Jens; Otte, Kerstin
Abstract: Chinese hamster ovary (CHO) suspension cells are the main production hosts for biopharmaceuticals. For the improvement of production processes, it is essential to understand the interaction between CHO cells and their microenvironment. While the cellular membrane is the crucial surface barrier between the inner and outer cell compartments, the subgroup of cell surface proteins (surfaceome) is of particular interest due to its potential to react to external factors and initiate cell communication and interaction pathways. Therefore, the CHO surfaceome was explored for the first time by enriching exposed N‐glycosylated membrane proteins before tandem mass spectrometry (MS/MS) analyses, identifying a total of 449 surface proteins, including 34 proteins specific for production cells. Functional annotation and classification located most proteins to the cell surface belonging mainly to the protein classes of receptors, enzymes, and transporters. In addition, adhesion molecules as cadherins, integrins, Ig superfamily and extracellular matrix (ECM) proteins as collagens, laminins, thrombospondin, fibronectin, and tenascin were significantly enriched, which are involved in mechanisms for the formation of cell junctions, cell–cell and cell–ECM adhesion as focal adhesions. As cell adhesion and aggregation counteracts scalable production of biopharmaceuticals, experimental validation confirmed differential expression of integrin β1 (ITGB1) and β3, CD44, laminin, and fibronectin on the surface of aggregation‐prone CHO production cells. The subsequent modulation of the central interaction protein ITGB1 by small interfering RNA knockdown substantially counteracted cell aggregation pointing toward novel engineering routes for aggregation reduction in biopharmaceutical production cells and exemplifying the potential of the surfaceome for specified engineering strategies. Abstract : In this study, the surfaceome of producing and nonproducing Chinese hamster ovary (CHO) cell lines was characterized for the first time applying cell surface capturing (CSC) before tandem mass spectrometry (MS/MS) analysis. The knowledge about proteins present on the surface of CHO cells led to the identification of mechanisms affecting cell aggregation, which is a major problem impairing biopharmaceutical production. A transient knockdown of integrin β1 resulted in reduced aggregation of a recombinant expressing CHO cell line, which was prone to form cellular aggregates.